2006
DOI: 10.2478/s11687-006-0019-8
|View full text |Cite
|
Sign up to set email alerts
|

Species of the nematode genus Amidostomum Railliet and Henry, 1909 in aquatic birds in the Netherlands

Abstract: 98 SummaryThe presence of gizzard worms belonging to the genus Amidostomum was studied in birds in the Netherlands during the period 1975 -2003. Amidostomum acutum was found in Anatidae: Anas acuta, A. clypeata, A. crecca, A. penelope, A. platyrynchos, A. strepera The prevalence is only given for bird species where ten or more individuals had been investigated: Anas platyrhynchos (n = 14): 21.4 %; Melanitta nigra (n = 12): 91.7 %; Somateria mollissima (n = 117): 100 %; Anser albifrons (n = 11): 100 % and Cygn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
9
0
5
Order By: Relevance
“…These parasites live under the chitinous layer of the gizzard, feeding on the blood of the host, and at a high intensity of infection can cause mass deaths (Borgsteede et al 2005, 2006; Thieltges et al 2006; Kats 2007). …”
Section: Introductionmentioning
confidence: 99%
“…These parasites live under the chitinous layer of the gizzard, feeding on the blood of the host, and at a high intensity of infection can cause mass deaths (Borgsteede et al 2005, 2006; Thieltges et al 2006; Kats 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Thieltges et al (2006) counted 416 worms in the most intensively infected eider in the Northern Wadden Sea, a slightly higher burden than the most intensive infection detected in the present study (302 worms). Previously, various authors also reported A. anseris to infect eiders, but a recent review considered the species to infect geese exclusively (representatives of Anser and Branta) (Borgstede et al, 2006). Two nematodes, found in the gizzard of every fourth eider in the study, were S. crassicauda and S. dogieli, but infections were usually restricted to a few worms (Table 2).…”
Section: Other Parasitesmentioning
confidence: 93%
“…Количественные показатели инвазии уток указанными гельминтами часто имеют очень высокие значения. В литературе неоднократно появлялись сообщения о массовых находках погибших особей обыкновенной гаги -как птенцов, так и взрослых птиц [2][3][4][5]. В качестве возможной причины гибели птиц авторы рассматривали именно высокую интенсивность инвазии разными паразитами.…”
unclassified
“…В качестве возможной причины гибели птиц авторы рассматривали именно высокую интенсивность инвазии разными паразитами. По результатам проведённых исследований можно выделить группу видов червей, потенциально опасных для жизни и здоровья гаг [2][3][4][5]. К ним следует отнести Paramonostomum alveatum (Trematoda: Notocotylidae), M. pygmaeus, Microsomacanthus microsoma (Cestoda: Hymenolepididae), а также P. phippsi и Polymorphus minutus (Palaeacanthocephala: Polymorphidae).…”
unclassified